Metal Oxides Derived from Modified Hydromagnesite: Evaluation of Their Catalytic Activity in the Synthesis of Ethyl Biodiesel - Guebara, Pamela F. [UNESP]; Perrone, Olavo M. [UNESP]; Siqueira, Marcos R. [UNESP]; Mancini, Marcelo [UNESP]; Da-Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; Boscolo, Mauricio [UNESP] (Wiley, 2019)
Biofuels are already part of the energy matrix in many countries because of their environmental and economic benefits. Ethyl biodiesel can be produced by various processes, the main one being transesterification of triglyceraldehydes and ethanol. The current technological challenge is to develop efficient heterogeneous catalysts, at low cost, non-polluting and recyclable to be used in this process. In this context, hydromagnesites Mg5(CO3)4(OH)2⋅4H2O modified with different cations (Ca2+, Zn2+, Cu 2+, Ba2+) and synthesized by co-precipitation are used as precursors of catalytic oxides calcined at 600 °C. The biodiesel synthesis was conducted at 120 °C for 12 h using 20% (w/w) of catalyst per mass of soybean oil and the ratio 1:20 (mol/mol) of soybean oil/ethanol. The alkyl esters formed were quantified by Gas Chromatography-Flame Ionization Detection (GC-FID). The transesterification reaction catalyzed by the reference oxide had a yield of 40%, whereas the best yield (80%) came from the hydromagnesite modified with 20% of Ca2+ which also had the highest basicity/acidity ratio. After use in three reaction cycles, the catalyst with 20% Ca2+ had no significant reduction in efficiency when it was washed with acetone and recalcined at 600 °C, while the untreated catalyst only had a yield of 42%, showing the need for effective reconditioning.
Keywords: Biomass; Catalytic transesterification; Ethyl biodiesel; Heterogeneous catalysis; Modified hydromagnesite